2018
DOI: 10.4103/jips.jips_219_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of implant-abutment connections, abutment angulations, and screw lengths on preloaded abutment screw using three-dimensional finite element analysis: An in vitro study

Abstract: The present study suggests selecting appropriate implant-abutment connection based on the abutment angulation, as well as preferring long screws with more number of threads for effective preload retention by the screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Bone is a complex living structure without a defined pattern, its actual mechanical properties are not precisely established and its characteristics vary among individuals. [ 31 32 ] The FEA model used in this study assumed completely rigid equating to full osseointegration before loading. Moreover, ideal conditions, such as 100% contact between bone and implant and perfect fit of implants, abutments, and prosthetic bars were ensured.…”
Section: Discussionmentioning
confidence: 99%
“…Bone is a complex living structure without a defined pattern, its actual mechanical properties are not precisely established and its characteristics vary among individuals. [ 31 32 ] The FEA model used in this study assumed completely rigid equating to full osseointegration before loading. Moreover, ideal conditions, such as 100% contact between bone and implant and perfect fit of implants, abutments, and prosthetic bars were ensured.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Cone beam computed tomography-guided implant placement in the anterior maxilla will overcome the possibility of an angulated abutments, yet expensive; hence, its use can be restricted to place multiple implants in the same region. [ 35 36 37 38 ] Therefore, further studies can be carried out with improvements made to finite element models with respect to geometry of implants with regard to thread pitch, thread shape, and thread depth, applying dynamic loading conditions depending on the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Screw length:One study recommends a long screw with more threads to increase screw retention,[ 9 ] while two other studies recommend the opposite. Of these two studies, the first one concluded that when a minimum length abutment screw was used (1.4 mm; 3.5 threads) there was hardly any difference in screw loosening post oblique cyclic loading compared with longer abutment screws.…”
Section: Factors Affecting Abutment Screw Looseningmentioning
confidence: 99%